The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1053/euje.2001.0111
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic Filling and Pressure Imaging: Taking Advantage of the Information in a Colour M-mode Doppler Image

Abstract: The ability to derive non-invasively information on left ventricular diastolic function on one hand and pressure gradients on the other hand, makes Doppler ultrasound a very attractive tool in clinical practice. However, the limitations of the standard Doppler approaches in differentiating between normal and pseudonormal filling patterns, together with the limitations of the simplified Bernoulli equation for assessing pressure gradients, are well described. In this manuscript the role of colour M-mode Doppler … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 73 publications
1
10
0
Order By: Relevance
“…The formation of a ring vortex during LV filling is predicted by numerical (Iudicello et al 1997;Vierendeels et al 2000) and in vitro simulations Shortland 1996;Steen and Steen 1994) and is in agreement with in vivo observed characteristics of LV filling Vierendeels et al 2002). Therefore, a v p value obtained from a CMD image can be associated with the propagation velocity of the ring vortex from the base towards the apex (Steen and Steen 1994;Vierendeels et al 2000;De Mey et al 2001;Vierendeels et al 2002). A convincing argument in our (and previous) observations is that E always exceeded v p , which agrees with the hydrodynamic principle that, due to the intrinsic circular motion of the particles in the ring vortex, the velocity of particles (E) in a vortex ring exceeds the velocity at which the whole ring travels (v p ).…”
Section: Cmd Echocardiography and Hydrodynamics Of LV Fillingsupporting
confidence: 67%
See 2 more Smart Citations
“…The formation of a ring vortex during LV filling is predicted by numerical (Iudicello et al 1997;Vierendeels et al 2000) and in vitro simulations Shortland 1996;Steen and Steen 1994) and is in agreement with in vivo observed characteristics of LV filling Vierendeels et al 2002). Therefore, a v p value obtained from a CMD image can be associated with the propagation velocity of the ring vortex from the base towards the apex (Steen and Steen 1994;Vierendeels et al 2000;De Mey et al 2001;Vierendeels et al 2002). A convincing argument in our (and previous) observations is that E always exceeded v p , which agrees with the hydrodynamic principle that, due to the intrinsic circular motion of the particles in the ring vortex, the velocity of particles (E) in a vortex ring exceeds the velocity at which the whole ring travels (v p ).…”
Section: Cmd Echocardiography and Hydrodynamics Of LV Fillingsupporting
confidence: 67%
“…In the quest to differentiate between normal and pseudonormal LV filling patterns, different pathways have been followed (De Mey et al 2001). In this study we focused on v p as measured using CMD echocardiography.…”
Section: Cmd Echocardiography and Hydrodynamics Of LV Fillingmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, CMD echocardiography and the CMD-derived parameter ''flow propagation velocity'' have attracted the attention of cardiologists as a new method to evaluate diastolic function of the LV. Five different approaches (Brun et al 1992;Stugaard et al 1993Stugaard et al , 1997Takatsuji et al 1996;Duval-Moulin et al 1997) have been used to obtain flow propagation velocity from a color M-mode Doppler echocardiogram (De Mey et al 2001). Although these studies have shown the usefulness of CMD echocardiography for assessing LV filling flow, because of the complexity of the pattern of blood flow in the LV as well as the limited amount of information obtained by using these methods, theoretical bases of the relationship between pattern of a CMD echocardiogram and LV diastolic function have not been elucidated.…”
mentioning
confidence: 99%
“…The measured velocity is presented in an M-mode image called a CMD echocardiogram. Evaluation of LV diastolic function is made based on a CMD echocardiogram colour pattern (DE MEY et al, 2001).…”
mentioning
confidence: 99%